The twelfth Imam - Rosenberg, Joel C. 1967- (Carol Stream, Illinois : Tyndale House Publishers, 2010)
As the apocalyptic leaders of Iran call for the annihilation of Israel and the U.S., CIA operative David Shirazi is sent into Tehran with one objective: use all means necessary to disrupt Iran's nuclear weapons program, without leaving American fingerprints and without triggering a regional war. A native Farsi speaker whose family escaped from Iran in 1979, he couldn't be better prepared for the mission. But none of his training has prepared Shirazi for what will happen next. An obscure religious cleric is suddenly hailed throughout the region as the Islamic messiah known as the Mahdi or the Twelfth Imam. News of his miracles, healings, signs, and wonders spreads like wildfire, as do rumors of a new and horrific war. Shirazi must take action to save his country and the world, but the clock is ticking.
Keywords: Intelligence officers -- United States -- Fiction; Suspense fiction